Singlet Oxygen in Food: A Review on Its Formation, Oxidative Damages, Quenchers, and Applications in Preservation - Limei Xiao; Shoujing Zheng; Zhengrong Lin; Chunyan Zhang; Hua Zhang; Jiebo Chen; Lu Wang (Antioxidants, 2025)
Singlet oxygen (1O2) has been proven to simultaneously cause oxidative damage to food and the death of microorganisms. In order to enhance the utilization of 1O2 in food systems, this review presents an overview of recent studies on the formation mechanisms of 1O2, the damage mechanisms of 1O2 on food, the self-protective mechanisms in food against 1O2, and the applications of 1O2 in food preservation based on the narrative review guidelines. Studies have shown that in vegetable and meat systems, 1O2 is mainly produced through photochemical reactions. It has been suggested that proteins and lipids are the main target compounds for oxygen in food. Natural antioxidants in food (such as vitamin E and carotenoids) can remove 1O2 through physical or chemical quenching mechanisms. Novel preservation techniques featuring a thin film technology coupled with photosensitizers have been employed on the surface of food to prolong the shelf life. However, how to balance the bactericidal effect of 1O2 and its oxidative effects on food still requires further research. It could be feasible that 1O2 will play an increasingly important role in the future food industry on the premise of strengthening supervision over food safety risks induced by 1O2.